Geotechnical risk-informed decision-making in mining - Lupo, J.F. (MGR 2019: Proceedings of the First International Conference on Mining Geomechanical Risk, 2019)
Uncertainty and variability are ever-present in the fields of geomechanics and geotechnical engineering. These uncertainties and variabilities can introduce risk into mine facilities (open pits, underground, tailings storage facilities, etc.). Traditionally, the Factor of Safety (FS) has been used as a measure of anticipated performance. In other words, if the FS meets the acceptance criteria, it is anticipated that the facility will perform in an acceptable manner. However, the FS, by itself, does not communicate anything about risk, nor variability or uncertainty. Reliability methods allow calculation of a Probability of Failure (PF), which can be integrated into a risk assessment. However, a PF assumes that all of the critical elements of a design have been adequately addressed. In either case, the FS and PF, by themselves, are of limited utility if performance measures (deformation, piezometric head, etc.) are not also defined as part of the acceptance criteria. Risk-informed decision-making (RIDM) provides an avenue to make informed risk decisions while providing a platform for defining the acceptance criteria. In this approach, there is a direct link between risk and performance. The RIDM process also allows the risk and acceptance criteria to be updated periodically, so that changes in the operation and/or performance can be considered. This approach is in contrast to the current practice where acceptance criteria are often defined without regard to the site conditions and where risk and acceptance criteria are treated as constants.